2021
DOI: 10.29271/jcpsp.2021.03.258
|View full text |Cite
|
Sign up to set email alerts
|

Progression and Resolution of COVID-19 Pneumonia on Chest Radiograph

Abstract: Objective: To evaluate the temporal changes on serial chest radiographs (CXRs)of hospitalised COVID-19 positive patients till their outcome(discharge/death); to determine the severity of CXR score and its correlation with clinical outcome (hospital stay, chest intubation and mortality). Study Design: Descriptive study. Place and Duration of Study: Shifa International Hospital (SIH), Islamabad from March to June 2020. Methodology: After IRB approval, 112 patients were consecutively enrolled, having laboratory-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…17 We assessed the radiological severity of the disease using CXR rather than HRCT to reduce expenses as Masood et al describe X-Ray findings in COVID Pneumonia. 19 Similarly Rashid et al elaborate the role of CXR in COVID-19 pneumonia, discouraging the wastage of resources. 20 The patients having normal SpO 2 at rest after recovery from COVID-19 develop dry cough of variable intensity, aggravated at night or early morning and similar in character to bronchial asthma.…”
Section: Discussionmentioning
confidence: 99%
“…17 We assessed the radiological severity of the disease using CXR rather than HRCT to reduce expenses as Masood et al describe X-Ray findings in COVID Pneumonia. 19 Similarly Rashid et al elaborate the role of CXR in COVID-19 pneumonia, discouraging the wastage of resources. 20 The patients having normal SpO 2 at rest after recovery from COVID-19 develop dry cough of variable intensity, aggravated at night or early morning and similar in character to bronchial asthma.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in many studies involving imaging modalities. Asghar MS et al 4 and Masood L et al 5 described lung involvement on X-ray chest. Asghar et al 4 reported "bilateral lower zone patchy infiltrates as frequent chest X-ray finding" Regarding modality of CT scan chest Asefi H et al commented that "at least in earlier stages of the disease, CT may not be valuable as a screening test for COVID-19".…”
Section: Discussionmentioning
confidence: 99%
“…In addition, considering that only the first or admission chest radiograph was included in this study, it is possible that the pattern of disease may have shifted towards consolidation predominance on later, serial images given the authors’ subsequent understanding of the temporal changes of COVID-19 pneumonia on imaging. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Architectural distortion, subpleural lines and septal thickening were also identified in one study in the lower lobes predominantly, all of which are signs seen more commonly in the resorptive stage of the disease, indicating local inflammatory absorption with residual fibrosis and associated bronchus distortion. 31,32,40 Diffuse bronchiectasis with background emphysema was found in one patient with COPD. There were no pleural or pericardial effusions, lung nodules or tree-in-bud pattern to suggest other acute comorbid lung diseases; however, the small number of CTs makes it difficult to determine the significance of these findings.…”
Section: Computed Tomography Findingsmentioning
confidence: 99%
See 1 more Smart Citation